Image-Guided Hypofractionated Radiotherapy in Low-Risk Prostate Cancer Patients. (23rd April 2014) - Valeriani, Maurizio; Carnevale, Alessia; Agolli, Linda; Bonome, Paolo; Montalto, Adelaide; Nicosia, Luca; Osti, Mattia F.; De Sanctis, Vitaliana; Minniti, Giuseppe; Maurizi Enrici, Riccardo
Abstract : Aim . To evaluate efficacy and toxicity of image-guided hypofractionated radiotherapy (HFRT) in the treatment of low-risk prostate cancer. Outcomes and toxicities of this series of patients were compared to another group of 32 low-risk patients treated with conventional fractionation (CFRT). Methods . Fifty-nine patients with low-risk prostate cancer were analysed. Total dose for the prostate and proximal seminal vesicles was 60 Gy delivered in 20 fractions. Results . The median follow-up was 30 months. The actuarial 4-year overall survival, biochemical free survival, and disease specific survival were 100%, 97.4%, and 97.4%, respectively. Acute grade 1-2 gastrointestinal (GI) and genitourinary (GU) toxicity rates were 11.9% and 40.7%, respectively. Grade 1 GI and GU late toxicity rates were 8.5% and 13.6%, respectively. No grade ≥2 late toxicities were recorded. Acute grade 2-3 GU toxicity resulted significantly lower (P = 0.04 ) in HFRT group compared to the CFRT group. The cumulative 4-year incidence of grade 1-2 GU toxicity was significantly higher (P < 0.001 ) for HFRT patients. Conclusions . Our study demonstrated that hypofractionated regimen provided excellent biochemical control in favorable risk prostate cancer patients. The incidence of GI and GU toxicity was low. However, HFRT presented higher cumulative incidence of low-grade late GU toxicity than CFRT.